ON THE QUESTION OF THE NEED FOR EXAMINATION PROJECTS OF INTERNATIONAL AGREEMENTS AND DECISIONS IN EURASIAN ECONOMIC UNION - Anar Сагидан (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2015)
The author reveals the necessity for examination of international treaties and decisions drafts of the Eurasian Economic Union, its content and principles; characteristics the regulatory impact assessment documents on the European Union example